Aplikasi Ilmu Biologi Dalam Pendidikan dan Pembangunan Berwawasan Lingkungan Berbasis Sumberdaya Alam - Ramadhanil Ramadhanil; Elijonnahdi Elijonnahdi (Biology Department, Mathematics and natural science, Tadulako University, 2011)
Biology is one of knowledge belong to basic sciences that have important roles in education and sustainable development that environmental sound. Biological science is a basic for numeral applied sciences such as Medicine, Pharmacy, Agriculture including Fishery, Animal husbandry, Forestry and soon. There is a branch of biology which have been developed rapidly namely Ecology that close related with environmental problem or sciences that study on the relationship between organism and their environment or interaction among environmental factors at a numerous ecosystem type such teresterial, fresh water, marine, forest and soon. Ecology is the study that may explain the cause of the occurrence of various phenomena and environmental issues that occur on Earth, such as floods, drought, landslides, the